ANALISIS HUKUM DISPENSASI KAWIN TANPA ALASANMENDESAK: STUDI KASUS PENETAPAN NOMOR442/PDT.P/2023/PA.KRW - Syifa Raisa Nurinsani; Bambang Daru Nugroho; Betty Rubiati (Pojok Publisher, 2025)
Child marriage remains a significant issue in Indonesia, despite existing regulations that set a minimum legal age for marriage. This study examines Court Decision Number 442/Pdt.P/2023/PA.Krw, which granted a marriage dispensation to a minor without any urgent justification. The legal issues addressed include the judge's considerations in granting the dispensation and the extent of judicial authority in applying the principle of ius curia novit in such cases. This research employs a normative juridical and descriptive-analytical approach, using secondary data such as court decisions, marriage law, child protection law, judicial authority law, and relevant literature. The results showed that the decision was contrary to the relevant positive law which expressly prohibits underage marriage without urgency as mandated in the legislation. Granting dispensation without urgent grounds risks undermining the government’s efforts to prevent child marriage. Therefore, stricter regulations and oversight are needed to ensure the protection of children's rights.